Acupuncture Intervention Protocol: Consensus Process for a Pragmatic Randomized Controlled Trial of Acupuncture for Management of Chronic Low Back Pain in Older Adults: An NIH HEAL Initiative Funded Project - Arya Nielsen PhD; Laura Ocker LAc, MAcOM; Iman Majd MD, MS, LAc; Jeff A Draisin MD; Katherine Taromina CACM, LAc; Marjorie T Maggenti LAc; Jaimie Long LAc; Mark Nolting ND, LAc; Karen J Sherman PhD, MPH (SAGE Publishing, 2021)
Objective The aim of this article is to describe the consensus process used to develop an acupuncture intervention protocol for an NIH-funded pragmatic randomized controlled trial (PRCT) of acupuncture for the management of chronic low back (cLBP) in older adults (BackInAction). Background CLBP is among leading causes of disability worldwide: almost 33% of US adults 65 and older experience LBP. Acupuncture is effective for cLBP but there is no specific data on older adults. The National Institutes for Health (NIH) funded a PRCT of acupuncture needling for this population. An essential trial milestone was development of a consensus intervention protocol. Methods An Acupuncture Advisory Panel (AAP) was formed with nine members: two physician-acupuncturists, six licensed acupuncturists representing diverse work backgrounds, and an acupuncture researcher. We used a modified Delphi process that included provision of acupuncture trial data, survey data describing how each expert treats cLBP, three conference calls, and between-call email discussion. Results Lively and professional discussions led to a consensus intervention protocol for the BackInAction trial that included steps/staging of care, recommendations for parameters of care session length, number of needle insertion sites, insertion depths, needle retention times, recommended types of needles, both local and distal areas of the body to be treated, acupuncture point options, auricular point options, self-care options, and minimum number of sessions considered ideal. Conclusion Using a modified Delphi process, an expert AAP created a consensus intervention protocol for the PRCT of acupuncture needling for cLBP in patients 65 and older.